Outsourcing and offshoring of professional services : business optimization in a global economy - Gupta, Amar (Information Science Reference, 2008)
"This book discusses the considerations and implications surrounding the outsourcing and offshoring of professional services, such as software development computer-aided design, and healthcare, from multiple global perspectives. This book, offers industry professionals, policymakers, students, and educators with a balance between a broad overview and detailed analysis of offshore outsourcing, would make an invaluable addition to any reference library"--Provided by publisher
"Premier reference source"--Cover
Keywords: Offshore outsourcing.; Contracting out.; elektronické knihy; electronic books